2017
DOI: 10.1111/imcb.1017
|View full text |Cite
|
Sign up to set email alerts
|

Importance of phosphoinositide binding by human β‐defensin 3 for Akt‐dependent cytokine induction

Abstract: Host defense peptides (HDPs) are well-characterized for their antimicrobial activities but also variously display potent immunomodulatory effects. Human β-defensin 3 (HBD-3) belongs to a well-known HDP family known as defensins and is able to induce leukocyte chemotactic recruitment, leukocyte activation/maturation, proinflammatory cytokine release, and co-stimulatory marker expression. HBD-3-stimulated cytokine induction is NF-κB-dependent and was initially suggested to act via G protein-coupled C-C chemokine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…PLC is a key signaling protein that plays a significant role in multiple physiological processes in cells. Previous studies have reported that AMPs can stimulate the release of cytokines via the activation of PLC signaling and have immunomodulatory effects [5,42]. The PLC-dependent pathway is involved in the A-hBD-2-induced production of cytokines and chemokines, as demonstrated by the inhibitory effects of U73122 against A-hBD-2 and confirmed by the decreased production of cytokines and chemokines.…”
Section: +mentioning
confidence: 85%
“…PLC is a key signaling protein that plays a significant role in multiple physiological processes in cells. Previous studies have reported that AMPs can stimulate the release of cytokines via the activation of PLC signaling and have immunomodulatory effects [5,42]. The PLC-dependent pathway is involved in the A-hBD-2-induced production of cytokines and chemokines, as demonstrated by the inhibitory effects of U73122 against A-hBD-2 and confirmed by the decreased production of cytokines and chemokines.…”
Section: +mentioning
confidence: 85%
“…Coincidentally, HBD‐3 can bind a range of phospholipids, including PIP2, which is important for its tumor cell permeabilization (30). Additionally, interaction of HBD‐3 with PIP2 was shown to be important for its immunomodulatory activity, particularly in PI3K‐Akt–NF‐κB–mediated cytokine induction of TNF and IL‐6 (54). Recently, HBD‐2 was also shown to bind several phospholipids, including PIP2 (28).…”
Section: Discussionmentioning
confidence: 99%
“…Defensins are a major family of HDPs and are ubiquitously found throughout the plant and animal kingdoms, where they play a vital role in innate defense, forming part of the chemical arsenal for the protection of their hosts (8, 9). In plants, these small (4554 aa), basic, cysteine‐rich proteins are well documented for their antimicrobial activities against a range of fungi and bacteria (1012). They are also able to inhibit proteinases, α‐amylases, and protein translation in eukaryotic and prokaryotic cell‐free systems (1315), block ion channels (16, 17), or confer stress tolerances, such as to salinity and metal zinc (18–20).…”
mentioning
confidence: 99%
“…Some pro-inflammatory properties of hBD-3 have been previously described. hBD-3 can induce inflammatory response by itself, through CCR6 binding or the G protein-coupled receptor (GPCR) and phospholipase C (PLC) signaling pathway, leading to the release of several cytokines such as IL-6, IL-10, IL-37, IFN-γ, CXL-10, CCL-2 and CCL-5 by human keratinocytes [ 55 , 56 ]. It can also modulate the response to TLR agonists.…”
Section: Discussionmentioning
confidence: 99%